Vegetarian diet as a risk factor for depression - Asanova, Azize (Psychosomatic Medicine and General Practice, 2017)
Almost every person tried to practice some diet at least once in own life. But it’s little known about the health effects that can have a severe restriction of certain food products, especially, if this diet is vegetarian.